Gamma knife stereotactic radiosurgical thalamotomy for intractable tremor: A systematic review of the literature. Issue 3 (March 2015) - Campbell, Allison M.; Glover, Janis; Chiang, Veronica L.S.; Gerrard, Jason; Yu, James B.
Abstract Tremor markedly reduces quality of life and causes a significant psychological burden for patients who are severely affected by this movement disorder. Pharmacologic and surgical treatments for tremor exist, but for patients who have failed medical therapy and are not surgical candidates, stereotactic radiosurgery is the only available treatment option. Of available stereotactic radiosurgical techniques for intractable tremor, the authors chose to evaluate the safety and efficacy of gamma knife stereotactic radiosurgical thalamotomy. In order to qualitatively synthesize available data a systematic review was conducted by searching MEDLINE (OvidSP 1946–January Week 1 2014) and Embase (OvidSP 1974–2014 January). The search strategy was not limited by study design or language of publication. All searches were conducted on January 7, 2014. Treatment efficacy, adverse outcomes, and patient deaths were reviewed and tabulated. Complications appeared months to years post procedure and most commonly consisted of mild contralateral numbness and transient hemiparesis. Rarely, more severe complications were reported, including dysphagia and death. Though no data from randomized controlled trials are available, our analysis of the literature indicates that unilateral gamma knife thalamotomy using doses from 130 to 150 Gy appears safe and well tolerated.